2018
DOI: 10.1097/ccm.0000000000003281
|View full text |Cite
|
Sign up to set email alerts
|

Low Interleukin-7 Receptor Messenger RNA Expression Is Independently Associated With Day 28 Mortality in Septic Shock Patients*

Abstract: Supplemental Digital Content is available in the text.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
9
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 41 publications
2
9
0
Order By: Relevance
“…Both IL7R3 and IL7R7 transcripts expressions were decreased in septic shock patients’ T cells (Fig. 2), as we previously observed in whole blood [8]. While whole blood IL7R3 and IL7R7 expressions may be impacted by sepsis-induced lymphopenia, these transcripts are also intrinsically regulated in T cells.
Fig.
…”
supporting
confidence: 75%
See 1 more Smart Citation
“…Both IL7R3 and IL7R7 transcripts expressions were decreased in septic shock patients’ T cells (Fig. 2), as we previously observed in whole blood [8]. While whole blood IL7R3 and IL7R7 expressions may be impacted by sepsis-induced lymphopenia, these transcripts are also intrinsically regulated in T cells.
Fig.
…”
supporting
confidence: 75%
“…Several transcripts missing the exon 6, coding for the transmembrane domain have been identified, such as IL7R3 [4, 6] and IL7R7 (Ensembl). We recently showed that plasmatic sCD127 concentration and whole blood IL7R3 transcript expression were decreased in septic shock [7, 8]. However, sCD127 protein and transcripts regulations in survivor and non-survivor patients differed, with higher sCD127 concentration and lower IL7R3 expression in non-survivors.…”
mentioning
confidence: 99%
“…This could account for an unequal distribution in the initial infectious site as it is reported that the expression of these genes is impacted by the site of the initial infection in sepsis 47 . In accordance, the identified "severe" cluster gathers the expression of genes associated with poor outcome and high mortality described in previous studies 30,[46][47][48] . Interestingly, the SEB-based IFA also identified S3 and SV3 clusters of septic patients who seem to display an intermediate-to-severe phenotype.…”
Section: Discussionsupporting
confidence: 88%
“…The clusters S2 and SV2, that could be considered as the “severe” clusters, included all the non-survivors at day 28 who did not develop any HAI before death (n = 4 in the discovery cohort and n = 3 in the validation cohort). Of note, genes previously described in subgroups of septic patients as being associated with mortality were, herein, found to be modulated specifically in the “severe” cluster in the discovery ( DIRK2 , ADGRE3 , CCNB1IP1 30 , and IL7R/CD127 46 ) and validation ( MDC1 30 and IFI44L 47 ) cohorts. This could account for an unequal distribution in the initial infectious site as it is reported that the expression of these genes is impacted by the site of the initial infection in sepsis 47 .…”
Section: Discussionmentioning
confidence: 49%
“…Quantification of the IL-7 receptor gene expression in the blood helps to identify patients with sepsis at risk of death. 107 The neutrophil transcriptome is a promising new source of biomarkers in sepsis with lipocalin-2 (also known as gelatinase-associated lipocalin) and matrix metallopeptidase 8 among the most promising ones. 108,109 Transcriptomics could identify endotypes of sepsis with distinct clinical and biological features and differential treatment responses.…”
Section: Lack Of Standardisation Of Immunological Test For Clinical Amentioning
confidence: 99%